Embedding social relations into primary care: A population‐based approach. What matters most? Population practice of social ecology in medicine and communities - Helen Mary Kingston; Frances da Cunha (Wiley, 2022)
Abstract Background The importance of social connectedness has long been an area of research in medical research. The damaging impact of social isolation is recognised and proven. This article describes our experiences of embedding routine enquiry about networks of support into routine clinical care. Aims The majority of care happens through the strength of bonds and support between the network of immediate family and friends. Acknowledging these networks and actively working to support them is central to health and wellbeing. Results In parallel, working to improve professional networks builds trust, shared understanding and stronger relationships that benefit us all. The strengthening of bonds across and between teams delivering health care can benefit those working within them and lead to improved outcomes for both staff and patients. Conclusion Developing Frome as a compassionate community has enabled improved patient care, improved staff wellbeing and financial savings for the health community.